Socio-economic aspects of medical errors and their consequences in medical organizations - O. L. Zadvornaya; Yu. E. Voskanyan; I. B. Shikina; K. N. Borisov (Модернизация, инновация, развитие, 2019)
Medical errors and adverse events are a global problem of strategic importance, accompanied by economic costs that impose a burden on the health care system, the country's economy and society as a whole. The article presents the results of a review of world experience in developing approaches to assessing the safety of medical care in medical organizations, systematization and analysis of factors affecting the patient safety.Purpose: the purpose of the article is to study and assess the risks associated with medical errors and adverse events in the activities of medical organizations that affect the patient safety in order to reduce the loss of public health, improve the system of identification and monitoring of risk indicators that affect the safety of medical care.Methods: the method of rapid assessment and content analysis of published evidence, including who experience in safety of medical care, was used to highlight the issue. The methodology of functional benchmarking, which included the collection and analysis of the necessary information, the choice of individual functions, processes, methods of work of medical organizations working in similar conditions, was used in the study.Results: the approaches allowing to predict occurrence and development of risks in ensuring safety of medical care, reduction of losses of public health and social and economic costs of the state are considered and offered.Conclusions and Relevance: the materials presented in the article show that safety is a fundamental principle of providing medical services to patients and a critical component of the quality management system of medical care. To reduce the loss of public health, direct and indirect socio-economic costs of the state, comprehensive efforts are needed to reduce the risks that threaten the patient safety and improve the activities of medical organizations.